A Cross-Sectional Analysis of Musculoskeletal and Functional Outcomes in Patients with Pituitary Disorders: Frailty and Sarcopenia - Ugur, Kader; Gur, Mustafa; Mizrak, Mithat; Eryesil, Hasan; Hohluoglu, Abdulvahap; Artas, Hakan; Lee, Do-Youn (Mdpi, 2026)
Background/Objectives: The purpose of this study was to compare the prevalence of sarcopenia and frailty in patients with acromegaly and hypopituitarism to healthy controls. Methods: This descriptive, comparative study included 32 patients with acromegaly, 24 patients with hypopituitarism, and 28 healthy volunteers who had undergone abdominal computed tomography (CT) within a month of their presentation at the endocrinology outpatient clinic between October 2023 and October 2024. The Tilburg Frailty Indicator was used to measure frailty. Sarcopenia was assessed using a dynamometer to measure handgrip strength and a CT-derived skeletal muscle index (SMI) at the L3 spinal level to measure muscle mass. Results: Both the hypopituitarism (7.5 +/- 2.8) and acromegaly (7 +/- 2.7) groups had substantially greater frailty ratings than the controls (4.8 +/- 2.9) (p = 0.015). Frailty prevalence was 43% in the control group, 75% in acromegaly, and 83% in hypopituitarism (p = 0.019). The hypopituitarism group's muscle strength (20.8 +/- 7.4 kg) was substantially lower than that of the acromegaly (37.5 +/- 14.3 kg) and control groups (36.4 +/- 9.6 kg) (p < 0.001). Patients with hypopituitarism had substantially lower SMI values (45.1 +/- 11.3 cm2/m2) than those with acromegaly (53 +/- 8.9 cm2/m2) (p = 0.04). A total of 50% of the control group, 9% of those with acromegaly, and 54% of those with hypopituitarism had probable or confirmed sarcopenia (p < 0.001). Conclusions: This study shows that frailty is more prevalent in patients with acromegaly and hypopituitarism than in healthy controls, with sarcopenia being especially noticeable in hypopituitarism. After adjusting for age and sex, the association with frailty remained significant for hypopituitarism (OR = 5.24, p = 0.021) while acromegaly showed a borderline trend (OR = 3.00, p = 0.076). These results imply that pituitary hormones might contribute to maintaining the functional ability and integrity of the musculoskeletal system. Further research in prospective studies using population-based controls is necessary to examine screening for frailty and sarcopenia in patients with pituitary diseases.
Keywords: acromegaly; frailty; hypopituitarism; muscle strength; sarcopenia